Sustainable polymers from biomass: Bridging chemistry with materials and processing. (February 2020) - Wang, Zhongkai; Ganewatta, Mitra S.; Tang, Chuanbing
Graphical abstract: Abstract: Renewable natural resources, such as plant oils, fatty acids, cellulose, and lignin, have been widely pursued as precursors for manufacturing sustainable polymers. There are many challenges in the production of biobased plastics. This Trend article provides a succinct overview of three major areas: lignin chemistry and polymers, biobased polyolefins, and long-chain aliphatic polycondensates. The emphasis is placed on how chemistries of monomers and polymers improve materials properties in conjunction with processing methods. Each section concludes with challenges and prospects toward better sustainable polymers.